2003
DOI: 10.1074/jbc.r300009200
|View full text |Cite
|
Sign up to set email alerts
|

In Vivo Mutagenesis of the Insulin Receptor

Abstract: Mice bearing targeted gene mutations that affect insulin receptor (Insr) function have contributed important new information on the pathogenesis of type 2 diabetes. Whereas complete Insr ablation is lethal, conditional mutagenesis in selected tissues has more limited consequences on metabolism. Studies of mice with tissue-specific ablation of Insr have indicated that both canonical (e.g. muscle and adipose tissue) and noncanonical (e.g. liver, pancreatic ␤-cells, and brain) insulin target tissues can contribut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
16
0

Year Published

2005
2005
2014
2014

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 71 publications
0
16
0
Order By: Relevance
“…In contrast, complete disruption of the IR gene leads to insulin resistance, diabetes and shortened lifespan (Okamoto & Accili, 2003). Likewise, tissue-specific IR knockout mouse models develop obesity, insulin resistance and impaired glucose regulation, with the exception of fat-specific IR knockout mice (FIRKO) (Okamoto & Accili, 2003). These mice have reduced fat mass, are protected against age-related obesity and live longer than their littermates.…”
Section: Insulin/igf-1 Signalling (Iis)mentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, complete disruption of the IR gene leads to insulin resistance, diabetes and shortened lifespan (Okamoto & Accili, 2003). Likewise, tissue-specific IR knockout mouse models develop obesity, insulin resistance and impaired glucose regulation, with the exception of fat-specific IR knockout mice (FIRKO) (Okamoto & Accili, 2003). These mice have reduced fat mass, are protected against age-related obesity and live longer than their littermates.…”
Section: Insulin/igf-1 Signalling (Iis)mentioning
confidence: 99%
“…Furthermore, mice mutated for the IGF-1 receptor hint at a direct role for reduced IGF-1 signalling in mammalian longevity: Igf1r +/-females, but not males, exhibit a long-lived phenotype (Holzenberger et al ., 2003). In contrast, complete disruption of the IR gene leads to insulin resistance, diabetes and shortened lifespan (Okamoto & Accili, 2003). Likewise, tissue-specific IR knockout mouse models develop obesity, insulin resistance and impaired glucose regulation, with the exception of fat-specific IR knockout mice (FIRKO) (Okamoto & Accili, 2003).…”
Section: Insulin/igf-1 Signalling (Iis)mentioning
confidence: 99%
“…skeletal muscle and adipose tissue, and non-canonical insulin targets, e.g. liver, pancreas and brain tissues, may contribute in distinctly different ways to clinical insulin resistance (Okamoto and Accili, 2003). The insulin receptor represents a tyrosine kinase, whereby insulin binding to the a-subunits causes the b-subunits to autophosphorylate, thus activating the catalytic activity of the receptor complex.…”
Section: Introductionmentioning
confidence: 99%
“…For example, knockout of INSR in white adipose tissue protects mice against obesity, whereas its elimination in brown adipose lead to the development of b-cell failure (see 101 for detailed analysis). By using microsatellite markers, analysis of linkage and familybased association, it was concluded that the INSR gene marker D19S884, which is located 1 cM telometric to the INSR gene, is significantly associated with PCOS (v 2 = 11.85; P < 0.0006).…”
Section: Insulin Signalling Pathway: Ins Inrs Akt2 Glut4 and Irs Gmentioning
confidence: 99%